Study on the Electrochemical Co-Reduction of Gd(III) and Al(III) in LiF-CaF2 Melt. Issue 9 (1st January 2018) - Chen, Zi; She, Changfeng; Zheng, Haiyang; Huang, Wei; Zhu, Tiejian; Jiang, Feng; Gong, Yu; Li, Qingnuan
Abstract : This paper describes the co-reduction process of Gd-Al alloys and the electrochemical extraction of gadolinium from gadolinium oxide in LiF-CaF2 melt. Gd2 O3 was fluorinated by adding AlF3, and dissolved into the melt as Gd(III). The electrochemical behaviors and alloy forming mechanisms of Gd(III) and Al(III) were analyzed through cyclic voltammetry, square wave voltammetry, chronopotentiometry, and open circuit chronopotentiometry. Potentiostatic electrolyses in the LiF-CaF2 -Gd2 O3 -AlF3 system were conducted for three hours under −1.60 V and −2.20 V, respectively, and at least three kinds of Gd-Al alloys were obtained. The GdAl3 phase was identified through a scanning electron microscope equipped with an energy dispersive spectrometer (SEM-EDS) and X-ray diffraction analysis, and GdAl2 and GdAl were characterized by SEM-EDS.